Pianificazione ambientale autosostenibile e alimentazione: il Piano del cibo della Provincia di Pisa - Butelli, Elisa (Scienze del Territorio, 2015)
The Food plan of the Province of Pisa was founded to build an alliance between city and countryside with the objective of protecting food production and environmental resources, granting to all citizens access to healthy and sustainable food, and ensuring a more adequate level of income for farmers. The Province, with the scientific support of the University of Pisa, launched in 2010 the development of the Food plan, opening a reflection on sustainable planning connected to food, analyzing and comparing the needs of the citizen with the existing network of local producers and involving a multiplicity of public and private partners. Thanks to the network created among professionals in the health care business and researchers from different Faculties of the University, it built a space of multidisciplinary dialogue, collaboration and planning, to create shared rules and promote collective knowledge on the theme of food and its implications on society, health, environment, economy and production. Food democracy actions were thus lunched, developing civic innovation paths pointed at improving eating habits and reduce waste, involving citizens and institu-tions in helping the construction of a city model able to maintain a virtuous relationship between community and territorial well-being.